Histopathological Evaluation of Non-Obstructive Azoospermic Males Using Testicular aspirate (TESA) biopsy - Karbel Hadeel A.1 , Al -Bdairi Adnan A.2 , Khairullah Ahmed R.3 , Al-Humairi Ameer K.4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Male infertility considers a real diagnostic challenge because of several factors have beeninvolved in its pathogenesis. Histopathology of the testicular biopsy consider the corner stone in thediagnosis. The aim of this study is to report the utility of using of Testicular aspirate biopsy (TESA) for theevaluation of the male infertility & compare the outcomes with different parameters.Materials & methods: we design prospective study for 205 infertile males with Non -Obstructive azoospermiawho referred to the Teeba IVF & genetic center for the period from December 2016 to December 2018, theyunderwent bilateral TESA for histopathological evaluation & 45 patients out of 205 male had previous opentesticular biopsy. The hormonal profile for all patient. were done. Results: among 205 patients underwentTESA procedure the commonest histopathological pattern was spermatocyte maturation arrest, present in113 patients (55.1%) followed by round maturation arrest in 41 (20%). There was a good degree of agreementbetween the spermatogenesis scoring according to TESA and open surgical biopsy (P=< 0.001). The plasmalevels for both LH & FSH were statistically showing significant differences in their levels according to theTESA spermatogenesis scoring. (P<0,001).Conclusion: the utility of TESA biopsy in the evaluation oftesticular biopsy from Azoospermic males is significantly associated with the histopathological pattern ofspermatogenesis & hormonal profile.